2008
DOI: 10.1080/14613800802079080
|View full text |Cite
|
Sign up to set email alerts
|

Investigating musical performance: commonality and diversity among classical and non-classical musicians

Abstract: The Investigating Musical Performance: Comparative Studies in Advanced Musical Learning research project was devised to investigate how classical, popular, jazz and Scottish traditional musicians deepen and develop their learning about performance in undergraduate, postgraduate and wider music community contexts. The aim of this paper is to explore the findings relating to attitudes towards the importance of musical skills, the relevance of musical activities and the nature of musical expertise. Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 12 publications
3
66
0
1
Order By: Relevance
“…In a questionnaire-based study investigating classical and non-classical (pop, jazz and folk) early career performing musicians, Creech et al (2008) obtained ratings from participants on factors they considered important to their de elopment Classical musicians rated instrumental teachers, parents, musical events and professional colleagues as the most important musical influences, while non-classical musicians reported that their most important influences were well-known performers and significant musical events.' p 22 ; the st dy did not loo at the q estion of m sical infl ence in general ho e er Academics must come to terms with previous research just as musicians negotiate their position with music history, and one attention-demanding text from literary criticism is Harold Bloom's The Anxiety of Influence Bloom 7 Bloom's essential arg ment re ol es aro nd a poet's tro led relationship ith strong predecessors, and the various ways a great poet can finally win out in the battle (chiefly by a s fficiently charismatic misreading' of their predecessor's or The eight of history only increases o er time to stifle latecomers ' Transplanting the tensions to m sic m sicologists ha e found the theory partially prod cti e in s ch cases as Brahms's or in the s pposed shado of Beetho en or Chopin (Korsyn, 1991), compositional relations between twentieth century composers (Straus, 1991;Schwarz et al, 2008), or outside of the classical tradition in studies of Keith Emerson (Kawamoto, 2005) or Syrian and Moroccan Andalusian musics (Shannon, 2007).…”
Section: University Of Sussexmentioning
confidence: 99%
“…In a questionnaire-based study investigating classical and non-classical (pop, jazz and folk) early career performing musicians, Creech et al (2008) obtained ratings from participants on factors they considered important to their de elopment Classical musicians rated instrumental teachers, parents, musical events and professional colleagues as the most important musical influences, while non-classical musicians reported that their most important influences were well-known performers and significant musical events.' p 22 ; the st dy did not loo at the q estion of m sical infl ence in general ho e er Academics must come to terms with previous research just as musicians negotiate their position with music history, and one attention-demanding text from literary criticism is Harold Bloom's The Anxiety of Influence Bloom 7 Bloom's essential arg ment re ol es aro nd a poet's tro led relationship ith strong predecessors, and the various ways a great poet can finally win out in the battle (chiefly by a s fficiently charismatic misreading' of their predecessor's or The eight of history only increases o er time to stifle latecomers ' Transplanting the tensions to m sic m sicologists ha e found the theory partially prod cti e in s ch cases as Brahms's or in the s pposed shado of Beetho en or Chopin (Korsyn, 1991), compositional relations between twentieth century composers (Straus, 1991;Schwarz et al, 2008), or outside of the classical tradition in studies of Keith Emerson (Kawamoto, 2005) or Syrian and Moroccan Andalusian musics (Shannon, 2007).…”
Section: University Of Sussexmentioning
confidence: 99%
“…Given the apparent lack of literature on band rehearsing of popular music within higher education curricula (Creech et al, 2008;Daniel, 2006;Lebler, 2007), despite there being a number of studies involving group work practice, there is a demonstrated need to further investigate this particular rehearsal environment and its associated pedagogy.…”
Section: Introductionmentioning
confidence: 99%
“…These are the main genres performed in public by undergraduate music students in Scotland and are the categories used by other researchers in this area (e.g. Creech, et al, 2008).…”
Section: Introduction Musical Genres As Communities Of Practicementioning
confidence: 99%